Peripersonal Space: An Index of Multisensory Body–Environment Interactions in Real, Virtual, and Mixed Realities - Serino, Andrea; Noel, Jean-Paul; Mange, Robin; Canzoneri, Elisa; Pellencin, Elisa; Ruiz, Javier Bello; Bernasconi, Fosco; Blanke, Olaf; Herbelin, Bruno (Frontiers in ICT, 2018)
Human-environment interactions normally occur in the physical milieu, and thus by medium of the body and within the space immediately adjacent to and surrounding the body; the peri-personal space (PPS). However, human interactions increasingly occur with or within virtual environments, and hence novel approaches and metrics must be developed to index human-environment interactions in virtual reality (VR). Here we present a multisensory task that measures the spatial extent of human PPS in real, virtual, and augmented realities. We validated it in a mixed reality ecosystem in which real environment and virtual objects are blended together in order to administer and control visual, auditory, and tactile stimuli in ecologically valid conditions. Within this mixed-reality environment, participants are asked to respond as fast as possible to tactile stimuli on their body, while task-irrelevant visual or audio-visual stimuli approach their body. Results demonstrate that, in analogy with observations derived from monkey electrophysiology and in real environmental surroundings, tactile detection is enhanced when visual or auditory stimuli are close to the body, and not when far from it. We then calculate the location where this multisensory facilitation occurs as a proxy of the boundary of PPS. We observe that mapping of PPS via audio-visual, as opposed to visual alone, looming stimuli results in sigmoidal fits – allowing for the bifurcation between near and far space – with greater goodness of fit. In sum, our approach is able to capture the boundaries of PPS on a spatial continuum, at the individual-subject level, and within a fully controlled and previously laboratory-validated setup, while maintaining the richness and ecological validity of real-life events. The task can therefore be applied to study the properties of peri-personal space in humans and to index the features governing human-environment interactions in virtual or mixed reality. We propose PPS as an ecologically valid and neurophysiologically established metric in the study of the impact of VR and related technologies on society and individuals.